Implementation Of Passenger Analysis Unit (PAU) From The Perspective Of Immigration Law Enforcement At The Immigration Checklist Of I Gusti Ngurahrai International Airport - Sulistian, Muhammad Rizki; Silalahi, W (Universitas Muhammadiyah Sumatera Utara, 2025)
Utilization of Passenger Analysis Unit (PAU) technology is a strategic step in modernizing the Immigration Management Information System (SIMKIM) in accordance with Law Number 6 of 2011 concerning Immigration. Although explicit regulations are not yet available, PAU has proven crucial in supporting immigration supervision, especially in early detection of security risks and violations of the law, such as increasing deterrence at Ngurah Rai Airport and identifying the Vladimir Dmitrievskii case. PAU empowers immigration officers through fast and comprehensive passenger data analysis to maintain national security and sovereignty, especially in the work area of the Class I Special Immigration Office TPI Ngurah Rai. Optimizing PAU requires the preparation of comprehensive regulations and SOPs, increased coordination between agencies, and ongoing training for immigration officers